2020
DOI: 10.2147/ijn.s240232
|View full text |Cite
|
Sign up to set email alerts
|

<p>Green Synthesis, Characterization and Antimicrobial Activity of Copper Oxide Nanomaterial Derived from <em>Momordica charantia</em></p>

Abstract: Background: In the emerging field of nanotechnology, copper oxide (CuO) nanomaterials are considered to be one of the most important transition metal oxides owing to its fascinating properties. Its synthesis from green chemistry principles is gaining importance as next-generation antibiotics due to its simplicity, eco-friendliness, and cost-effectiveness. In the present study, CuO nanorods (CuO NRs) were synthesized from the aqueous fruit extract of Momordica charantia and characterized using different analyti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
55
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 109 publications
(66 citation statements)
references
References 47 publications
11
55
0
Order By: Relevance
“…Natural plant products are an important source to control bacterial pathogens. Therefore, in the present study, a poly-herbal tooth powder was redesigned to toothpaste form, it was standardized as per the guidelines [ 15 , 16 , 17 ] and evaluated for antibacterial activity which has showed significant results.…”
Section: Discussionmentioning
confidence: 99%
“…Natural plant products are an important source to control bacterial pathogens. Therefore, in the present study, a poly-herbal tooth powder was redesigned to toothpaste form, it was standardized as per the guidelines [ 15 , 16 , 17 ] and evaluated for antibacterial activity which has showed significant results.…”
Section: Discussionmentioning
confidence: 99%
“…For the preparation of biogenic CuO nanomaterial our previous protocol was followed [ 16 ]. In order to synthesize CuO, a 0.1 M solution of CuSO 4 .5H 2 O was added to an aqueous extract of MC in a ratio of 1:3 ( v / v ) (pH 11) and was heated to 50 °C, followed by a washing and drying process.…”
Section: Methodsmentioning
confidence: 99%
“…To address all of the above issues, the present study proposes a simplified, highly versatile, and efficient method that can be employed for the design of stable nanocomposites. Previous studies have shown that CuO nanomaterial synthesized from Momordica charantia (MC) exhibits a thin layer of phytochemicals present in aqueous extracts that lead to agglomeration and the formation of unstable particles [ 16 ]. A novel method compiling green synthesized CuO nanomaterial from MC and phospholipids extracted from egg yolk in combination with glycerol has been presented.…”
Section: Introductionmentioning
confidence: 99%
“…CuO-NPs were biosynthesized by the actinomycetes and enhanced antimicrobial activity was reported by Nabila and Kannabiran (2018) against some bacterial pathogens. Similarly, Qamar et al (2020) synthesized CuO-NPs from Momordica charantia plants with improved antibacterial activity against different bacterial pathogens such as Bacillus cereus , Corynebacterium xerosis , and Streptococcus viridians.…”
Section: Role Of Nanotechnology In Crop Protectionmentioning
confidence: 99%